Analysis of the function of IL-10 in chickens using specific neutralising antibodies and a sensitive capture ELISA. (October 2016) - Wu, Zhiguang; Hu, Tuanjun; Rothwell, Lisa; Vervelde, Lonneke; Kaiser, Pete; Boulton, Kay; Nolan, Matthew J.; Tomley, Fiona M.; Blake, Damer P.; Hume, David A.
Abstract: In mammals, the inducible cytokine interleukin 10 is a feedback negative regulator of inflammation. To determine the extent to which this function is conserved in birds, recombinant chicken IL-10 was expressed as a secreted human Ig Fc fusion protein (chIL-10-Fc) and used to immunise mice. Five monoclonal antibodies (mAb) which specifically recognise chicken IL-10 were generated and characterised. Two capture ELISA assays were developed which detected native chIL-10 secreted from chicken bone marrow-derived macrophages (chBMMs) stimulated with lipopolysaccharide (LPS). Three of the mAbs detected intracellular IL-10. This was detected in only a subset of the same LPS-stimulated chBMMs. The ELISA assay also detected massive increases in circulating IL-10 in chickens challenged with the coccidial parasite, Eimeria tenella . The same mAbs neutralised the bioactivity of recombinant chIL-10. The role of IL-10 in feedback control was tested in vitro . The neutralising antibodies prevented IL-10-induced inhibition of IFN-γ synthesis by mitogen-activated lymphocytes and increased nitric oxide production in LPS-stimulated chBMMs. The results confirm that IL-10 is an inducible feedback regulator of immune response in chickens, and could be the target for improved vaccine efficacy or breeding strategies. Highlights: Five mouse mAbs to chicken IL-10 was produced. Two capture ELISA assays were developed to quantify native IL-10. Three mAbs (ROS-AV162, 163 and 164) neutralised the bioactivities of chIL-10. Anti-IL-10 antibodies detected intracellular IL-10 in only a subset of LPS-stimulated macrophages. Eimeria infection of chickens produced a massive increase in circulating IL-10.